2023
DOI: 10.3389/fphar.2022.1092501
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical administration for severe hypertension during pregnancy: Network meta-analysis

Abstract: Aims: To evaluate the efficacy of different pharmacologic treatment for severe hypertension during pregnancy.Methods: Two reviewers searched Ovid MEDLINE, Ovid EMbase, and the Cochrane Library for randomized clinical trials from the establishment of the database to 15 July 2021 that were eligible for inclusion and analyzed the pharmaceuticals used for severe hypertension in pregnancy.Results: 29 relevant trials with 2,521 participants were involved. Compared with diazoxide in rate of achieving target blood pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 71 publications
(131 reference statements)
0
1
0
Order By: Relevance
“…The selection of antihypertensive drugs and the route of administration depends on (i) the initial diagnosis, (ii) the expected delivery time and (iii) the presence or absence of preeclampsia and also preferences and experience of attending physicians. A recent comprehensive network meta-analysis indicated that nifedipine could be recommended as a strategy for BP management in pregnant women with severe hypertension and that labetalol and hydralazine showed in fact limited efficacy [1084]. However, in cases of preeclampsia with severe features, persistent severe hypertension or recurrent severe hypertension despite orally administered agents, i.v.…”
Section: Hypertension In Specific Settingsmentioning
confidence: 99%
“…The selection of antihypertensive drugs and the route of administration depends on (i) the initial diagnosis, (ii) the expected delivery time and (iii) the presence or absence of preeclampsia and also preferences and experience of attending physicians. A recent comprehensive network meta-analysis indicated that nifedipine could be recommended as a strategy for BP management in pregnant women with severe hypertension and that labetalol and hydralazine showed in fact limited efficacy [1084]. However, in cases of preeclampsia with severe features, persistent severe hypertension or recurrent severe hypertension despite orally administered agents, i.v.…”
Section: Hypertension In Specific Settingsmentioning
confidence: 99%